Early childhood teachers’ understanding of executive functions and strategies employed to facilitate them - Madanipour, Parian; Garvis, Susanne; Cohrssen, Caroline; Pendergast, Donna (Frontiers in Education, 2025)
IntroductionAdult-child interactions have a noteworthy influence over how executive functions develop. However, despite recognising the importance of executive functions in a child’s success, little research has been undertaken to explore the role of early childhood teachers in facilitating the development of executive functions in children through their teaching practice. The current study thus explored what understanding early childhood teachers have of executive functions and what pedagogical practices they use to contribute to the development of executive functions in 3 to 5-year-old children within preschool settings.MethodsData were collected through an online questionnaire completed by 58 early childhood teachers across Victoria, Australia. The questionnaire included both closed and open-ended questions, aiming to explore participants’ understanding of executive functions and the specific pedagogical practices they employed to facilitate the development of these skills in their classroom. Qualitative data from open-ended responses were analysed thematically to identify recurring practices and perceptions.ResultsThe results reveal that some early childhood teachers reported strong pedagogical understanding of executive functions. Further, they reported implementing practices in the everyday classroom intended to promote executive functions. Thematic analysis of qualitative data reveals that these early childhood teachers apply five pedagogical practices intended to facilitate executive functions: environment and activity structuring, supporting autonomous behaviours, enacting purposeful classroom organisation, encouraging sustained shared thinking, and conducting activities that support executive functions.DiscussionThe self-reported data in this study suggest that some early childhood teachers know much about evidence-based pedagogical practices that facilitate children’s executive functions. The reported pedagogical practices employed by such teachers aligned closely with practices recommended in the literature. However, participants’ pedagogical understanding was reported to have been gained through experience, drawing attention to the need for a stronger focus on executive functions during initial teacher education courses. As such, this study highlights the need for Australian early childhood initial teacher education courses to ensure that executive functions and executive functions-supportive pedagogical practices are explicitly addressed. The insights revealed here should inform initiatives that raise awareness and understanding of executive functions among early childhood teachers to forefront executive functions during their time spent with preschoolers.